Experiences and challenges of enrolled nurses undertaking a Bachelor of Nursing Science programme in Namibia - Daniel O. Ashipala; Paulus K. Kapula; Alice Lifalaza (AOSIS, 2024)
Background: Globally, enrolled nurses (ENs) are embarking on an educational journey to become registered nurses (RNs) in order to enhance their knowledge and career opportunities. However, their aspiration is not without challenges. In Namibia, the experiences of these nurses have not been extensively researched. Objectives: This study aims to explore and describe the experiences and challenges of ENs undertaking a Bachelor of Nursing Science at the University of Namibia. Method: A qualitative, exploratory, descriptive and contextual research strategy was followed as the basis of conducting the study. A sample of 15 nursing students was purposively selected from the target population of 73 nursing students. This sample size was determined by the saturation of data as reflected in repeating themes. The collected data were analysed thematically using an inductive approach. Results: Three main themes subsequently emerged from the study: ENs' positive experiences advancing in the Bachelor of Nursing Science (BNSc) programme; nurses' negative experiences advancing in the BNSc programme; and recommendations to ensure effective advancement in the BNSc programme Conclusion: The findings of this study revealed that ENs positively experience becoming a RN when it comes to self-development; however, they have negative experiences such as not receiving exemptions for prior learning and having to learn a new curriculum. Contribution: These findings may be used by the Faculty of Health Sciences, School of Nursing and Public Health management in order to develop targeted interventions and ongoing strategies during their curriculum review cycles to ensure positive student experiences and success within the programme.